Taking science to the moon : lunar experiments and the Apollo Program - Beattie, Donald A. (New series in NASA history., 2001)
"How did science get aboard the Apollo rockets, and what did scientists do with the space allotted to them? Taking Science to the Moon describes, from the perspective of NASA headquarters, the struggle that took place to include science payloads and lunar exploration as part of the Apollo program. Author Donald A. Beattie - who served at NASA from 1963 to 1973 in several management positions and finally as program manager, Apollo Lunar Surface Experiments - here supplies a detailed, insider's view of the events leading up to the acceptance of science activities on all the Apollo missions."--Jacket.